2023
DOI: 10.1136/bmjresp-2022-001498
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, severity and risk factors for asthma in school-going adolescents in KwaZulu Natal, South Africa

Abstract: BackgroundAsthma remains highly prevalent, with more severe symptoms in low-income to middle-income countries (LMICs) compared with high-income countries. Identifying risk factors for severe asthma symptoms can assist with improving outcomes. We aimed to determine the prevalence, severity and risk factors for asthma in adolescents in an LMIC.MethodsA cross-sectional survey using the Global Asthma Network written and video questionnaires was conducted in adolescents aged 13 and 14 from randomly selected schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
1
Order By: Relevance
“…Another cross-sectional study following the Phase I ISAAC protocol conducted in the air pollution priority area (City of Ekurhuleni Metropolitan Municipality) in Gauteng Province, South Africa, reported a higher prevalence of EE (14%) among 3424 adolescents aged 13 and 14 years old; however, the study reported a lower prevalence of current ESs (9.6%) compared to our findings [40]. Subsequently, a recent Global Asthma Network (GAN) study, including 3957 adolescents aged 13 to 14 years old in KwaZulu Natal Province, South Africa, reported a lower prevalence of AE (7.1%) compared to our study [61].…”
Section: Discussioncontrasting
confidence: 99%
“…Another cross-sectional study following the Phase I ISAAC protocol conducted in the air pollution priority area (City of Ekurhuleni Metropolitan Municipality) in Gauteng Province, South Africa, reported a higher prevalence of EE (14%) among 3424 adolescents aged 13 and 14 years old; however, the study reported a lower prevalence of current ESs (9.6%) compared to our findings [40]. Subsequently, a recent Global Asthma Network (GAN) study, including 3957 adolescents aged 13 to 14 years old in KwaZulu Natal Province, South Africa, reported a lower prevalence of AE (7.1%) compared to our study [61].…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple studies have corroborated the poor usage and non-adherence to metred dose inhalers in childhood asthma as a major barrier to care 11 17. This is further seen with the low levels of inhaled corticosteroids (6.7–17%) and 73% of doctor-diagnosed/suspected asthma not using any inhaler documented 6 31. Over-reliance on short-acting beta agonist inhalers per se is also a barrier to appropriate care 32.…”
Section: Discussionmentioning
confidence: 99%